The role of ERK1/2 signaling in diabetes: pathogenic and therapeutic implications - Xu, Hanlin; Liu, Tao; Dai, Yanfen; Li, Na; Cao, Zhanqi (Frontiers in Pharmacology, 2025)
ERK1/2 (extracellular signal-regulated kinase 1/2) is an important member of the MAPK (mitogen-activated protein kinase) family and is widely involved in many biological processes such as cell proliferation, differentiation, apoptosis and migration. After activation by phosphorylation, ERK1/2 can be transferred into the nucleus and directly or indirectly affect the activity of transcription factors, thereby regulating gene expression. More and more studies have shown that ERK1/2 plays an important role in diabetes and its complications, such as insulin secretion, islet β cell function, diabetic cardiomyopathy, diabetic nephropathy, renal fibrosis, lipogenesis, diabetic vasculopathy, etc. These effects reveal the complexity and diversity of the ERK1/2 signaling pathway in the pathogenesis of diabetes, and its activation and inhibition mechanisms in multiple physiological and pathological processes provide potential targets for diabetes treatment. The purpose of this mini-review is to explore the key role of ERK1/2 in diabetes and the progress of research on targeted inhibitors of ERK1/2, which provides new strategies for the treatment of diabetes.